Limb Necrosis Caused by Sclerotherapy When Treating Venous Malformation. (2016) - Zhou, P.; Chen, Y.; Chen, Z.
Abstract : Introduction: Percutaneous interventional sclerotherapy has been widely used to treat venous malformation. Satisfactory results have been reported, along with both mild and severe complications. Report: A 1.5 year old girl was diagnosed as having a venous malformation of the right vulva and right inner thigh. The patient received sclerotherapy using polidocanol. After the surgery, the right foot and lower leg became pale, and then, a few days later, necrotic. Conclusion: Accurate diagnosis and appropriate treatment are challenging for vascular malformations and should only be carried out in centers with ample expertise. Highlights: Interventional sclerotherapy has been widely used to treat venous malformations. Satisfactory results have been reported along with both mild and severe complications. There are no literature reports of limb necrosis, caused by sclerotherapy, requiring amputation. Treatment of vascular malformations should only be carried out in expert centers with ample expertise.